Prevalence of vitamin D deficiency in a North London antenatal population. (16th November 2010) - Parisaei, M; Clements, J; Govind, A; Arora, P; Lakshmi, H; Kapila, P
Abstract : Background: Calcium levels in adults depend heavily on concentration of vitamin D, and its deficiency in a pregnancy may lead to impairment of fetal skeletal formation and increase chronic disease susceptibility for the neonate. Women with darker skin produce less vitamin D for a given sunlight exposure and veiled women or those with modest dress code, regardless of the climate, have a reduced skin exposure to sunlight. Aim: The purpose of our study was to determine the prevalence of vitamin D deficiency in pregnant woman at time of booking at North Middlesex University Hospital, London. Material and Methods: This was a prospective study of maternal levels of vitamin D at booking. The hospital serves a borough where more than 50% of the local population is black and/or from ethnic minorities. Recruitment took place from March 2008 to March 2009. Results: 300 women were recruited during this period. The ethnic mix of this group was varied with 32% (n=97) of European origin, 27% (n=81) Africans and 11% (n=32) of women from Turkey. 80% of women, however regardless of ethnicity were vitamin D deficient at booking. Although the overall levels of vitamin D deficiency in our cohort were surprising, the increased prevalence in recognised high risk groups (ie, dark skinned/veiled women) correlates with published data. Conclusion: Further work is needed to locally introduce (National Institute for Health and Clinical Excellence) guidelines for vitamin D supplementation in pregnancy and audit its efficacy following implementation.